Ventilatory efficiency in post-COVID-19 athletes - Komici, K.; Bencivenga, L.; Rengo, G.; Bianco, A.; Guerra, G. (Physiological Reports, 2023)
Limitation in exercise capacity has not been described in athletes affected by SARS-CoV-2 infection. However, patients who have recovered from COVID-19 without cardiopulmonary impairment show exaggerated ventilatory response during exercise. Therefore, we aimed to evaluate the ventilatory efficiency (VEf) in competitive athletes recovered from COVID-19 and to characterize the ventilation versus carbon dioxide relationship (VE/VCO2) slope in this population. Thirty-seven competitive athletes with COVID-19 were recruited for this study. All participants underwent spirometry, echocardiography, and cardiopulmonary exercise testing (CPET). z-FVC values and end-title pressure of CO2 (PETCO2) were lower in the third tertile compared with the first tertile: -0.753 ± 0.473 vs. 0.037 ± 0.911, p = 0.05; 42.2 ± 2.7 vs. 37.1 ± 2.5 mmHg, p < 0.01. VE/VCO2 slope was significantly correlated to maximal VCO2/VE and maximal VO2/VE: coefficient = -0.5 R2 = 0.58, p < 0.0001 and coefficient = -0.3 R2 = 0.16, p = 0.008. Competitive athletes affected by SARS-CoV-2 infection, without cardio-respiratory disease sequel, may present ventilatory inefficiency (ViE), without exercise capacity limitation. FVC is higher in athletes with better ventilatory performance during exercise, and increased VE/VCO2 slope is inversely correlated to max VCO2/VE and max VO2/VE.